Mimpi Anak yang Tertunda : Ketika Harapan Orang Tua menjadi Tujuan Hidup Anak - Dea Alya; Maria Marsella; Natasya Bintang; Hairani Siregar (Pusat Riset dan Inovasi Nasional, 2025)
This study investigates how children’s personal aspirations are often overshadowed or replaced by their parents’ expectations, resulting in life paths that reflect family ambitions rather than individual desires. Focusing on university students, it explores the psychological tension and identity conflict caused by internalizing parental hopes as life goals. Using a qualitative approach through in-depth interviews and thematic analysis, the study captures diverse socio-economic experiences. Three main themes emerge: (1) emotional obligation to fulfill parental dreams, (2) identity confusion stemming from restricted personal agency, and (3) delayed self-actualization. While some students feel motivated by parental trust, others experience anxiety, emotional exhaustion, and suppressed personal aspirations. These findings form the conceptual framework of “borrowed dreams,” illustrating how intergenerational expectations shape identity and motivation. The study emphasizes the importance of improved family communication and culturally sensitive strategies to balance parental influence with youth autonomy. Recognizing young people’s right to define their own futures is vital for healthy identity development and well-being.